Promoting Collaboration in Supporting the Sustainable Governance of Educational Forest Areas - I Gede Eko Putra Sri Sentanu; Yuliannova Lestari; Georges Olemanu Lohalo (Publikasi Penelitian Terapan dan Kebijakan, 2023)
Agroforestry is designed to offer benefits to communities and improve community welfare. This research focuses on collaborative governance theory that intends to understand the history and management of agroforestry systems in UB Forest and related issues during the transition from Perhutani management to Universitas Brawijaya. The purpose is to understand issues related to agroforestry policies and regulations from the central/local government. This research adopts and confirms the theory developed by Ansell and Gash regarding collaborative governance. Case studies, including interviews, observations, and documentation were used in this research. The Mcnabb model technique was used in data analysis. The results show that the natural conversion of forests into agricultural land causes many problems, such as decreased soil fertility, erosion, extinction of flora and fauna, floods, droughts, and even changes in the global environment. It can be concluded that there are still some issues related to communication and commitment to the process. UB Forest adheres to the ministerial decree and the three pillars of higher education, but other actors have not committed because there is no written regulation.